Kazakh ThromboTest for intraoperative thrombosis risk assessment during stent-assisted cerebral aneurysm treatment: a single-center clinical study - Berdikhojayev, Mynzhylky; Maidan, Aiman; Makhanbetkhan, Shayakhmet; Sivasankar, Rajeev; Mussabekov, Maxat; Davletov, Dimash; Pons, Roger Barranco; Sarshayev, Marat (Frontiers in Neurology, 2025)
BackgroundStent-assisted endovascular treatment of cerebral aneurysms enhances long-term occlusion rates but carries a risk of thromboembolic complications, often influenced by resistance to antiplatelet therapy. Conventional platelet function tests, such as VerifyNow™, have limited predictive value and accessibility, particularly in resource-limited settings. The Kazakh ThromboTest (KTT) was developed as a real-time intraoperative method to detect thrombotic risk and guide antiplatelet management during neurointerventional procedures.MethodsWe retrospectively analyzed 284 patients who underwent stent-assisted aneurysm treatment at a single neurovascular center in Kazakhstan between 2020 and 2023, all of whom received dual antiplatelet therapy. The Kazakh ThromboTest (KTT) was performed intraoperatively in every case, and preoperative platelet reactivity was assessed using the VerifyNow™ P2Y12 assay.ResultsStent thrombosis occurred in 10 patients (3.52%), including 8 intraoperative and 2 delayed cases. KTT detected all intraoperative events, enabling immediate management such as conversion to balloon-assisted coiling. Among KTT-negative patients, delayed thrombosis occurred in 2 cases (0.7%). VerifyNow™ had no predictive value, as all thrombosis cases were classified as clopidogrel responders (≥50% inhibition). Multivariate analysis showed no association between thrombosis and sex, age, procedure duration, bleeding, clopidogrel timing, or VerifyNow™ inhibition. Thrombosis was, however, strongly linked to postoperative paresis or paralysis (p < 0.0001) and prolonged hospital stay (p = 0.0329).ConclusionThe Kazakh ThromboTest represents a practical and cost-effective intraoperative method with a high negative predictive value for identifying acute thrombotic risk during stent-assisted aneurysm repair. Despite adequate VerifyNow™ testing, KTT enabled timely procedural modifications, particularly in settings where standard platelet function assays are either unreliable or inaccessible. While VerifyNow™ did not predict thrombotic events, KTT contributed to safer procedural management and may serve as a valuable adjunct in neurointerventional practice.